The Punctum Fixum-Punctum Mobile Model: A neuromuscular principle for efficient movement generation? - von Laßberg, C.; Rapp, W. (PLOS ONE, 2015)
According to the "punctum fixum-punctum mobile model" that was introduced in prior studies, for generation of the most effective intentional acceleration of a body part the interseg-mental neuromuscular onset succession has to spread successively from the rotation axis(punctum fixum) toward the body part that shall be accelerated (punctum mobile). The aim of the present study was to investigate whether this principle is, indeed, fundamental for any kind of efficient rotational accelerations in general, independent of the kind of movements,type of rotational axis, the current body position, or movement direction. Neuromuscular onset succession was captured by surface electromyography of relevant muscles of the anterior and posterior muscle chain in 16 high-level gymnasts during intentional accelerating movement phases while performing 18 different gymnastics elements (in various body positions to forward and backward, performed on high bar, parallel bars, rings and trampoline), as well as during non-sport specific pivot movements around the longitudinal axis. The succession patterns to generate the acceleration phases during these movements were described and statistically evaluated based on the onset time difference between the muscles of the corresponding muscle chain. In all the analyzed movement phases, the results clearly support the hypothesized succession pattern from punctum fixum to punctum mobile. This principle was further underlined by the finding that the succession patterns do change their direction running through the body when the rotational axis (punctum fixum) has been changed (e.g., high bar or rings [hands] vs. floor or trampoline [feet]). The findings improveour understanding of intersegmental neuromuscular coordination patterns to generate intentional movements most efficiently. This could help to develop more specific methods to facilitate such patterns in particular contexts, thus allowing for shorter motor learning procedures of context-specific key movement sequences in different disciplines of sports, as wellas during non-sport specific movements.